Evaluación de un medio de cultivo para el aislamiento selectivo de campylobacters termotolerantes - Tresierra-Ayala, Álvaro (2018)
The ability of selective isolation of a culture medium for thermotolerant campylobacters, supplemented with pig blood and restrictive agents (bile salts, sodium thioglycollate, basic fuchsin), instead of the blood of sheep or horses and various antibiotics which are often components of the means commonly employed was evaluated. Twenty strains (13 C. coli y 7 C. jejuni) were isolated and identified from a total of 70 samples There was not significant difference with respect to the isolation ability between the culture medium evaluated and the modified Skirrow medium. For the comparative analysis about quantification of the growth of strains in both media, Miles and Misra technique, modified [1], was employed. So, it was determined that the strains showed no significant difference with respect to their growth on both media studied. Average growth of 23,4 x 106 and 21,7 x 106 CFU/ml for C. coli in culture medium evaluated and the modified Skirrow medium, and 44,6 x 106 and 40,1 x 106 CFU/ml for  C. jejuni in both culture media, respectively, were detected. Culture medium evaluated allows the same ability selective isolation of thermotolerant campylobacter than modified Skirrow medium; moreover, these microbial agents grow similarly quantitatively in both culture media.